A Critical-Hermeneutic Analysis of Shadow Politics Representation in the Godfather Trilogy - Vita Balqis D; Prasetya Yoga Santoso (The Easta Journal Law and Human Rights, 2026)
This study examines the representation of shadow politics in The Godfather trilogy using a critical-hermeneutic approach grounded in Paul Ricoeur’s narrative theory of Mimesis I–III. Shadow politics is conceptualized as informal power practices operating outside formal state institutions yet significantly shaping political decisions, legitimacy, and resource distribution. Employing qualitative narrative analysis, this study analyzes selected scenes, dialogues, and visual symbols from The Godfather (1972), The Godfather Part II (1974), and The Godfather Part III (1990) as political communication texts. Data analysis follows Miles and Huberman’s interactive model, complemented by Lasswell’s political communication framework to map actors, messages, channels, and effects within shadow power dynamics. The findings reveal that the mafia in the trilogy functions as a non-state political actor that substitutes and penetrates state functions, including justice, security, economic regulation, diplomacy, and leadership succession. Through Mimesis II, the films configure a parallel governance system sustained by patronage, loyalty, symbolic legitimacy, and controlled violence, while Mimesis III demonstrates how audiences may normalize or legitimize such informal power structures. Reflecting on the Indonesian political context after the 2024 elections, this study argues that The Godfather offers a critical lens to understand contemporary shadow political communication in transitional democracies, where procedural legality coexists with elite-driven informal decision-making. The study contributes conceptually by proposing the notion of shadow logic as a shared mindset underlying both criminal and formal political actors, enriching political communication and film studies by positioning cinema as a laboratory for critical analysis of power beyond formal institutions.